Dynamics of Microscale Precursors During Brittle Compressive Failure in Carrara Marble. Issue 6 (26th June 2019) - Kandula, Neelima; Cordonnier, Benoît; Boller, Elodie; Weiss, Jérôme; Dysthe, Dag Kristian; Renard, François
Abstract: Microscale heterogeneities influence failure mechanisms in the crust. To track the microstructural changes in rock samples when loaded until failure, we employed a novel experimental technique that couples dynamic X‐ray microtomography imaging with a triaxial deformation apparatus. We studied the brittle failure of Carrara marble under triaxial compression. Dynamic tomographic data revealed the spatial organization of microfractures and damage increments characterizing the precursory activity toward catastrophic failure. We quantified the emergence of scaling relationships between microstructural parameters, including total damage volume, incremental damage volume, the largest connected microfracture, and the applied differential stress. The total volume of microfractures accumulated from the beginning of the experiment as well as the incremental damage showed power law increase. The growth of the largest connected microfracture was related to differential stress as a power law with divergence at failure. The microfracture volume increments were distributed according to a power law with an upper cutoff that itself spanned the entire volume toward failure. These characteristic features of brittle failure in Carrara marble under compression are in agreement with theoretical models that consider failure as a critical phase transition. We also observed that, very close to failure, several power law relationships broke down, which we interpret to be related to the coalescence of the largest microfractures in a finite size volume. Scaling laws and associated exponents computed from our data are compared with predictions made from theoretical and numerical models. Our results show that precursors of macroscopic brittle failure in Carrara marble follow predictable trends. Key Points: Microfracture dynamics explains complex physical processes guiding the macroscopic failure in Carrara marble Statistical parameters measuring microfracture volume, growth, and spatial organization showed power law scaling with applied stress Evolution of several microstructural parameters is in agreement with models that establish compressive failure as a critical phase transition